2013
DOI: 10.1038/ejcn.2013.176
|View full text |Cite
|
Sign up to set email alerts
|

Measuring diet cost at the individual level: a comparison of three methods

Abstract: Background/objectives:Household-level food spending data are not suitable for population-based studies of the economics of nutrition. This study compared three methods of deriving diet cost at the individual level.Subjects/methods:Adult men and women (n=164) completed 4-day diet diaries and a food frequency questionnaire (FFQ). Food expenditures over 4 weeks and supermarket prices for 384 foods were obtained. Diet costs (US$/day) were estimated using: (1) diet diaries and expenditures; (2) diet diaries and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…In a series of studies A. Drewnowski and others have shown that processed foods are less expensive per calorie, which might explain the high intake of processed foods and the poor diets of low-income Americans (Drewnowski and Rehm, 2013a, b; Monsivais et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies A. Drewnowski and others have shown that processed foods are less expensive per calorie, which might explain the high intake of processed foods and the poor diets of low-income Americans (Drewnowski and Rehm, 2013a, b; Monsivais et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…This paper is not meant to impugn the motives or behaviors of low-income Americans, as the foods they consume are dependent on forces that have made unhealthy foods the least expensive per kilocalorie 5256 and have also led administrators to base SNAP on inadequate thrifty food plan costs. 415758 Subsequent papers in this Special Issue lay out the pros and cons of creating SNAP food or beverage restrictions to improve the diets of SNAP recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the utility of retailer presented via the O-D matrix of generalized cost of end-consumers (17). The generalized costs are calculated on models (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and the results of calculations are given in Table 5. Assessing the utility of retailer presented via the O-D matrix of generalized cost of end-consumers (1).…”
Section: Resultsmentioning
confidence: 99%
“…Determining the cost estimate of the energy costs of the human body in the purchasing process is based on the analysis of the required amount of calories for human existence (Postanova, 2000). According to the normative documents, the daily consumption of calories for normal functioning is 2790.8 kcal (Monsivais, et al, 2013). But this value may depend on gender, age, and the physical activity of a person.…”
Section: Estimation Of the Monetary Costs Of Endconsumer Fatiguementioning
confidence: 99%